Effect of nano hemoglobin-based oxygen carrier on radiosensitivity of lung cancer cell line - LIU Changmin; LI Yong; LI Fengjuan; ZHOU Wentao; HUANG Bingzhong; LIU Jiaxin; YANG Chengmin (Zhongguo shuxue zazhi)
[Objective] To study the effect of nano hemoglobin-based oxygen carrier (nano-HBOC) on radiosensitivity of lung cancer H385 cells. [Methods] Using 95% N2 and 5% CO2, a lung cancer cell line was constructed in a hypoxic environment, and H385 cells were treated with different concentrations of nano-HBOC and irradiated (4Gy) by an irradiator, and the IC50 concentration was calculated. The cells were detected by flow cytometry (reactive oxygen species, ROS) ROS test. Using GEO database, KEGG pathway enrichment analysis was carried out to predict possible pathways. The levels of lipid peroxidation and Fe2+ were observed by fluorescence microscope, and the proteins related to iron death pathway were detected by Western-blot. [Results] Compared with the control cells, the activity and density of the cells were significantly decreased by nano-HBOC combined with radiotherapy, with a notable proportion of cells exhibiting deteriorated status. There is a positive correlation between ROS level and nano-HBOC concentration, especially after radiotherapy. Radiotherapy combined with nano-HBOC significantly increased the levels of lipid peroxidation and Fe2+ in H385 cells, while decreasing the levels of iron death pathway proteins slc7a11 and GPX4, and increasing the level of ACSL4. [Conclusion] Nano-HBOC enhances the radiosensitivity of lung cancer H385 cells.